2019
DOI: 10.1177/1932296818818828
|View full text |Cite
|
Sign up to set email alerts
|

Peer Support Through a Diabetes Social Media Community

Abstract: Background: Caregivers and individuals living with type 1 diabetes (T1D) who are members of CGM in the Cloud, a Facebook group associated with the Nightscout Project, were interviewed to assess how the online community impacted peer support. Methods: Semistructured qualitative interviews were conducted with caregivers and patients who are part of CGM in the Cloud Facebook group. Interview transcripts were analyzed to identify various themes related to peer support in the online group. Results: Members of the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 13 publications
2
58
0
Order By: Relevance
“…The code granted him real-time access for monitoring his son's CGM data via the web or a smartphone app. Later, he made the Nightscout website and a private Facebook group called ''CGM in the Cloud'' to make the code openly available to a large community [16,22]. Pete Schwamb, a software engineer, invented RileyLink, a translator device to interconnect the insulin pump and an iPhone, in an effort to obtain access to the insulin pump data of his 6-year-old daughter Riley.…”
Section: D-dads: Chasing the Impossiblementioning
confidence: 99%
See 1 more Smart Citation
“…The code granted him real-time access for monitoring his son's CGM data via the web or a smartphone app. Later, he made the Nightscout website and a private Facebook group called ''CGM in the Cloud'' to make the code openly available to a large community [16,22]. Pete Schwamb, a software engineer, invented RileyLink, a translator device to interconnect the insulin pump and an iPhone, in an effort to obtain access to the insulin pump data of his 6-year-old daughter Riley.…”
Section: D-dads: Chasing the Impossiblementioning
confidence: 99%
“…An online survey reported that the patients and caregiver members of the ''CGM in the Cloud'' Facebook group have received and provided technical, emotional, and medical support through the online platform [22]. Patient stories and feedback are available at sites specific for different configurations of DIYAPS: https:// openaps.org, https://androidaps.readthedocs.…”
Section: Online Peer Support From the Loopers Communitymentioning
confidence: 99%
“…As smartphone and social media use are permeating individuals' lives, online peer support groups have become useful resources for exchanging ideas among people who undergo similar situations. In many chronic conditions, caregivers take advantage of exchanging useful health information and share experiences with other peers (37,38). Such opportunities to interact with individuals in similar circumstances enables caregivers to gain from indirect experiences and obtain useful resources, resulting in improved stress-coping strategies and resilience (36).…”
Section: Social Support: Ventilating Feelings and Acquiring Coping Stmentioning
confidence: 99%
“…In addition to that, support can extend to an extra experiences online forum, physically connecting its participants. (32) This space of exchange, especially for the young, can constitute an opportunity to re-signify the chronic disease, as well as to recognize among the shared difficulties some self-care strategies that can be adopted to improve their quality of life.…”
Section: M20 19 Yearsmentioning
confidence: 99%